Controlled formation of core–shell structures with uniform AlPO4 nanoshells1. Issue 14 (18th February 2015) - Yang, Fen-Li; Zhang, Wei; Chi, Zi-Xiang; Cheng, Fu-Quan; Chen, Ji-Tao; Cao, An-Min; Wan, Li-Jun
<x xml:space="preserve">Abstract</x> Uniform AlPO4 nanoshells are successfully achieved on different core materials by controlling their formation kinetics in solution.